THE PEOPLE'S PERCEPTION ON THE ROLE OF MASS MEDIA: A BANGLADESH STUDY - Choudhury, Anwar Hossain (International Journal of Research -GRANTHAALAYAH, 2021)
Background: Media is played the vital role in socialization process. Over the last one and half decades media have been receiving increasing amount of attention as an alternate Watchdog that think tanks in addressing many things. This study develops a framework of talk media socialization in Bangladesh. Methodology: This study was exploratory and descriptive in nature. Both quantitative and qualitative method applied for the collection of data through questionnaire survey interviews and case study. Results: The study shows that the present day media is highlighting a good number of reports on public sector corruption, education, public health, public policy, women empowerment etc. which have both tangible and intangible impacts. But the overall media role is way to reach at satisfactorily well and respondents expressed their reservation with media’s performance. People also believe media controlled by public influence. This study describes the terms political influence and communication level. Public opinion is made in democracy by watching responding to polls besides participating in elections. This research report tries to explain the agenda setting role of mass media during any crisis moment for building consensus of people in Bangladesh. This study investigates both positive and negative assorted influences on public discourses disseminated to Bangladeshi mass media.